The genetic determination of alternate stages in polyphenic insects - Erezyilmaz, D (Wiley, 2024)
Molt‐based transitions in form are a central feature of insect life that have enabled adaptation to diverse and changing environments. The endocrine regulation of these transitions is well established, but an understanding of their genetic regulation has only recently emerged from insect models. The pupal and adult stages of metamorphosing insects are determined by the stage specifying transcription factors broad‐complex (br) and Ecdysone inducible protein 93 (E93), respectively. A probable larval determinant, chronologically inappropriate metamorphosis (chinmo), has just recently been characterized. Expression of these three transcription factors in the metamorphosing insects is regulated by juvenile hormone with ecdysteroid hormones, and by mutual repression between the stage‐specific transcription factors. This review explores the hypothesis that variations in the onset, duration, and tissue‐specific expression of chinmo, br, and E93 underlie other polyphenisms that have arisen throughout insects, including the castes of social insects, aquatic stages of mayflies, and the neoteny of endoparasites. The mechanisms that constrain how chinmo, br, and E93 expression may vary will also constrain the ways that insect life history may evolve. I find that four types of expression changes are associated with novel insect forms: (1) heterochronic shift in the turnover of expression, (2) expansion or contraction of expression, (3) tissue‐specific expression, and (4) redeployment of stage‐specific expression. While there is more to be learned about chinmo, br, and E93 function in diverse insect taxa, the studies outlined here show that insect stages are modular units in developmental time and a substrate for evolutionary forces to act upon.